IS-Propaganda in der Türkei: die Onlinezeitschrift Konstantiniyye: ein Ein- und Überblick - Gögen, Sina (Grenzräume, Grenzgänge, Entgrenzungen, 2018)
The Global Jihad phenomenon and its boom caused by the terror organization Islamic State (IS) have gained international presence. This analysis focuses on their propaganda as a reason for its widespread success. As a bridge between western and eastern society structures, Turkey plays a crucial part in IS-strategies. Professional media propaganda is a key element of IS success. Therefore, this analysis concentrates on the first three issues of the Turkish IS-propaganda online magazine Konstantiniyye and its strategic as well as propagandistic contents. The analysis also demonstrates how the propaganda magazine is embedded in the Turkish context and which objective is pursued byspreading it out across Turkish-speaking people. Based on the results of a qualitative content analyses, it can be concluded that the structure of the propaganda magazine Konstantiniyye is in keeping with the structure of Jihadist propaganda. The organization is using the propaganda product Konstantiniyye effectively to spread its ideology amongst the Turkish population by employing classic propaganda methods. The organization accomplishes this by deliberately adapting its propaganda to the local context on the social as well as on the linguistic level. On the religious level however, the propaganda has not been adapted, but adheres to an understanding of religion that is in accordance with IS ideology. Consequently, the Turkish Islam, which is affected by nationalistic elements, seems to be rejected completely.